Investigation of the Perception of University Students Studying in Health Sciences on Interdisciplinary Team Work - Hatice Abaoğlu; Özge Buket Cesim; Sinem Kars; Semin Akel (Hacettepe University, 2018)
Objectives: The aim of this study was to evaluate the perception of university students studying in the field of health sciences on interdisciplinary teamwork. Materials and Methods: 265 university students of health sciences field aged between 18-25 participated in the study. Demographic characteristics of individuals, including age, gender, department and grade were recorded. In the study, Interdisciplinary Study Questionnaire which was created by the researchers was used as data collection tool. Results: Most of the individuals stated that they knew what the interdisciplinary study meant and it would be useful; they knew which professions were associated with their own profession; they would like to have fieldwork with students of other professions; and they wouldn't hesitate to ask for help from professionals outside their own field. It was found that individuals thought people in their profession did not consider themselves superior to other occupational groups; they were in good relationship with and interacted with those belonged to other professions; they tried to understand their skills and contributions and they wanted to share information and resources with them. Most of the individuals were of the opinion that the individuals in their profession were well-educated although had limited professional competence and autonomy. Conclusions: According to these results, it was concluded that students who study in the field of health sciences found interdisciplinary study important and useful. It is thought that individuals should be supported in terms of competence, autonomy and the awareness of the professional groups they will work with after graduation.